The Acceptance of New Religions on Java in the Nineteenth Century and the Emergence of Various Muslim and Christian Currents - Maryse Kruithof (Laboratorium Bantenologi UIN Sultan Maulana Hasanuddin Banten, 2017)
Abstract My Ph.D.- dissertation analyzes the work of six Dutch missionaries on Java in the period of 1850 until 1920. Besides analyzing their proselytizing strategies, I reserched on the missionaries’ reflections on their work and the reformed strategies that followed those reflections and their views on the religious context they worked in as well as how they perceived the process of admission of new religions. My focus is not only on the arrival and acceptance of Christianity, but also the Islamization process of Java, since the missionaries tried to elucidate that procesin order to benefit from it. As part of my dissertation, this paper will focus on the formation of various Muslim and Christian currents in the second half of the nineteenth century in order to elucidate the process of religious adaptation on Java.